Femme interventions and the proper feminist subject: Critical approaches to decolonizing western feminist pedagogies - Hoskin, Rhea Ashley (Cogent social sciences, 2017)
As it currently stands, little academic attention has been paid to the systematic devaluation of femininity or femmephobia. By adopting “femme” as a critical analytic, this paper dislocates femininity from its ascribed Otherness and demonstrates how empowered femininities have been overlooked within gender studies. Femme, as the failure or refusal to approximate the patriarchal norms of femininity, serves as the conceptual anchor of this study and is used to examine how femmephobic sentiments are perpetuated within Contemporary Western Feminist (CWF) theory. This perpetuation is propped up by the thematic marginalization of empowered femininities from the texts chosen for gender studies courses, revealing a normative feminist body constructed through the privileging of identities that maintains femininity as white, middle-class, normatively bodied, and without agency. The excavation of an empowered feminine subject from the margins reveals the foothold of normative whiteness embedded within feminist pedagogies. Using a thematic analysis of how femininity is taken-up within textbooks used in gender studies courses, the current paper demonstrates how intersections of femininity have yet to be addressed within dominant Feminist theories. The femme—as a queer potentiality—offers a way of (re)thinking through the limitations of CWF theory and the paradoxical preoccupations with the absented femme.